ANTROPOMETRIC CHARACTERISTICS AND MOTOR SKILLS OF YOUNG MONTENEGRO BASKETBALL PLAYERS - Milovan Ljubojević; Boris Nikolić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Testing and measurement in basketball is basically supposed to help in the initial evaluation and interpretation of features and capabilities of players that are important for their activity. The main objective of testing is the possibility of obtaining information about the three general indicators in basketball practice, namely: the level of current results in certain ability, the pace of results improvement in the ability and stability of the results in tests of ability. For this purpose, testing and measurement of young basketball players, members of the Montenegro under-18 team, was carried out. The aim of this paper is to present the basic features and capabilities of young basketball players of Montenegro and their comparison with some other teams. Variables from anthropometry space were measured: body height, arm span, reach height, body mass. Motor skills were observed by variables: the last squat, thrust from a flat bench, rear thrust, lying-sitting for 30 seconds, sargent test, long jump, 20 yard test, kamikaze, špagat, sitting bow. Based on the processed results it can be concluded that the motor skills of our young players, tested in this study, are at the level of the young players of other representations. The results will be of great help to coaches who work with these players.